A systematic meta-review of systematic reviews about interprofessional collaboration: facilitators, barriers, and outcomes. Issue 5 (3rd September 2022) - Wei, Holly; Horns, Phyllis; Sears, Samuel F.; Huang, Kun; Smith, Christopher M.; Wei, Trent L.
ABSTRACT: Interprofessional collaboration (IPC) is a practice model to promote healthcare quality. Since the World Health Organization highlighted the importance of IPC in 2010, a large volume of IPC-related research has been published. Multiple systematic reviews have been conducted to synthesize the literature from varying perspectives. Although systematic reviews are a compelling approach to synthesizing primary research, a systematic meta-review was needed to summarize the systematic reviews to offer information for healthcare professionals, researchers, and policymakers. This systematic meta-review was designed to synthesize the systematic reviews of IPC, emphasizing the IPC-related facilitators, barriers, and outcomes between 2010 and 2020. An electronic search for systematic reviews was performed in December 2020. The databases searched included PubMed, CINAHL, PsycINFO, and Cochrane Database of Systematic Reviews. Thirty-six systematic reviews met the inclusion criteria. Factors facilitating or impeding IPC were classified into three levels: organization, team, and individual. Major outcomes related to patients, healthcare professionals, and organizations. The facilitators, barriers, and outcomes are mutually interrelated. Highly effective collaboration is a process from relationship building to working together and collaborating. Improving IPC requires organizational, teams, and individuals' combined efforts. When highly effective collaborations occur, all stakeholders can benefit – organizations, professionals, and patients.